Mucosal Perfusion Preservation by a Novel Shapeable Tissue Expander for Oral Reconstruction - Barwinska, Daria (Plast Reconstr Surg Glob Open, 2017)
BACKGROUND: There are few methods for expanding oral mucosa, and these often cause complications such as tissue necrosis and expander eruption. This study examines mucosal blood perfusion following insertion of a novel shapeable hydrogel tissue expander (HTE). The canine model used subgingival insertion of HTE following tooth extraction and alveolar bone reduction. The primary goal of this study was to gain understanding of epithelial perfusion and reparative responses of gingival mucosa during HTE expansion. METHODS: Nine Beagle dogs underwent bilateral premolar maxillary and mandibular tooth extraction. Three to four months later, HTE-contoured inserts were implanted submucosally under the buccal surface of the alveolar ridge. After removal and following a 6- to 7-month period of healing, new HTE implants were inserted at the same sites. The area was assessed weekly for tissue perfusion and volume of expansion. Biopsies for histological analysis were performed at the time of expander removal. RESULTS: Within 2 weeks following the second insertion, blood flow returned to baseline (defined as the values of perfusion measurements at the presurgery assessment) and remained normal until hydrogel full expansion and removal. Volume expansion analysis revealed that the hydrogel doubled in volume. Histological assessment showed no macrophage or inflammatory infiltration of the mucosa. No superficial fibrosis, decreased vascularity, or mucosal change was seen. CONCLUSION: Maintenance of adequate tissue perfusion is a clinically important aspect of tissue expander performance to reduce risk of device loss or injury to the patient, particularly for areas with a history of previous surgeries.